Two-dimensional molybdenum disulfide artificial synapse with high sensitivity. Issue 1 (24th January 2022) - Huang, Hao; Liu, Lu; Jiang, Chengpeng; Gong, Jiangdong; Ni, Yao; Xu, Zhipeng; Wei, Huanhuan; Yu, Haiyang; Xu, Wentao
Abstract: This paper reports the fabrication of an artificial synapse (AS) based on two-dimensional molybdenum disulfide (MoS2 ) film. The AS emulates important synaptic functions such as paired-pulse facilitation, spike-rate dependent plasticity, spike-duration dependent plasticity and spike-number dependent plasticity. The spike voltage can mediate ion migration in the ion gel to regulate the conductance of MoS2 channel, thereby realizing the emulation of synaptic plasticity. More importantly, the AS stably exhibits high sensitivity in response to spike stimuli (100 mV) and low-energy consumption (∼33.5 fJ per spike). In addition, the device emulates some synaptic functions and realizes the synaptic expression of Morse code. The development of this device represents an important step toward constructing high-performance and multifunctional neuromorphic system.